2019
DOI: 10.1002/stem.3115
|View full text |Cite
|
Sign up to set email alerts
|

Fat grafting rescues radiation-induced joint contracture

Abstract: The aim of this study was to explore the therapeutic effects of fat grafting on radiation‐induced hind limb contracture. Radiation therapy (RT) is used to palliate and/or cure a range of malignancies but causes inevitable and progressive fibrosis of surrounding soft tissue. Pathological fibrosis may lead to painful contractures which limit movement and negatively impact quality of life. Fat grafting is able to reduce and/or reverse radiation‐induced soft tissue fibrosis. We explored whether fat grafting could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 17 publications
(20 reference statements)
0
19
0
1
Order By: Relevance
“…Clinically, autologous fat grafting has been adopted widely in reconstructive surgery because of its utility in tissue reconstruction and augmentation 25,26,56 . More recently, lipoaspirate, processed to retain different components of the stromal vascular fraction (SVF), has been promoted for its potential to improve healing and reverse scarring from traumatic injury 23 , burns 21,22 , and radiation 25,26 . There is, however, uncertainty regarding the efficacy of this procedure, and the underlying biological processes involved remain largely unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinically, autologous fat grafting has been adopted widely in reconstructive surgery because of its utility in tissue reconstruction and augmentation 25,26,56 . More recently, lipoaspirate, processed to retain different components of the stromal vascular fraction (SVF), has been promoted for its potential to improve healing and reverse scarring from traumatic injury 23 , burns 21,22 , and radiation 25,26 . There is, however, uncertainty regarding the efficacy of this procedure, and the underlying biological processes involved remain largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Adipocytes may also be involved in the matrix formation stages of wound healing, as they are closely associated with angiogenesis and production of collagen type VI in tissue from obese patients [17][18][19] . In addition, a growing number of clinicians have advocated for the use of fat autografts to reduce scarring and improve healing [20][21][22][23][24][25][26] . Other adipocyte-related cells, such as their precursors (i.e., pre-adipocytes and adipose derived stem cells (ASCs)), may also influence the healing process 20, [27][28][29][30] .…”
mentioning
confidence: 99%
“…Images of Picrosirius Red-stained slides were captured at 40 × and then color deconvoluted, converted to gray scale, binarized, and skeletonized using a novel algorithm run in MATLAB with Image Processing Toolbox (R2018b, MathWorks, Natick, MA) 41 . From the skeletonized images, 13 parameters of red collagen fibers were extracted (brightness, number, length, width, persistence, angle, branchpoints, euler number, extent, perimeter, solidity, eccentricity, equivalent diameter), measured using the regionprops command 42 , and underwent dimensionality reduction to generate 2 dimensional t-Distributed Stochastic Neighbor Embedding (TSNE) plots to visualize collective differences in the collagen fiber network patterns between groups. Geometric shapes were drawn to approximate the distribution of each cluster.…”
Section: Animals Female Adult 60-day-old Cd-1 Nude Immunocompromisedmentioning
confidence: 99%
“…Borrelli et al showed that fat grafting decreased dermal thickness and collagen production in a radiation-induced fibrotic skin mouse model. 66 Therefore, injecting ASCs immediately post-isolation will determine if soft priming is necessary for this cell type to elicit an improved healing response. Finally, while translationally relevant, our model of elbow contracture is a highly specific wound environment.…”
Section: Discussionmentioning
confidence: 99%